Coexistent Takayasu arteritis and sarcoidosis: A case report and review of the literature - Saha, Biplab Kumar; Burns, Stacey L; Foulke, Llewellyn; Judson, Marc A (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Takayasu Arteritis (TAK) is a granulomatous large vessel vasculitis that predominantly affects the aorta, major aortic branches and pulmonary arteries resulting in pulselessness. Sarcoidosis is a systemic granulomatous disease of unknown etiology that can affect any organ. Numerous cases of  coexistence of both these rare diseases have been described, suggesting that their association may be by more than chance alone. Objective: To describe a case of coexistent TAK and sarcoidosis and review the world literature concerning this condition. Methods: The clinical presentation and diagnostic approach is described of a woman with TAK who developed sarcoidosis. The world literature was reviewed by searching the PubMed and Google Scholar database for the terms ‘Takayasu arteritis’ and ‘sarcoidosis’; ‘Takayasu arteritis’ and ‘granuloma’; ‘vasculitis’ and ‘sarcoidosis’; and ‘vasculitis’ and ‘granuloma.’ The identified individual articles were reviewed, and the bibliography of these articles were scrutinized to identify more cases. The pertinent clinical features of these cases were summarized. Result: A 36-year-old Caucasian woman, who was diagnosed with histologically confirmed TAK at 22 years of age, was referred for evaluation of mediastinal lymphadenopathy. The diagnosis of sarcoidosis was established on histopathology of a mediastinal lymph node biopsy. A literature review identified 23 additional cases of coexisting sarcoidosis and TAK, and the clinical features of these cases is described. Conclusion: TAK and sarcoidosis may occur in the same patient. Given the prevalence of these diseases, concomitant development of these two diseases is unlikely to be by chance alone and probably reflects a unifying mechanism. Clinicians should be aware of this association in patients in order to make a timely diagnosis and optimize patient care.